Barriers to older adults' uptake of mobile-based mental health interventions. (February 2020) - Pywell, Jake; Vijaykumar, Santosh; Dodd, Alyson; Coventry, Lynne
Background: To address increasing demand of mental healthcare treatments for older adults and the need to reduce delivery costs, healthcare providers are turning to mobile applications. The importance of psychological barriers have been highlighted in the uptake of mobile-based mental health interventions and efforts have been made to identify these barriers in order to facilitate initial uptake and acceptance. However, limited research has focused on older adults' awareness of these applications and factors that might be hindering their use. Objective: The purpose of this study was to explore the perceived barriers that older adults experience in the uptake of mobile-based mental health interventions. Methods: Semi-structured interviews were conducted with a sample of 10 older adults, 50 years or older (female = 7, mean age = 68 years), who experienced periods of low mood. National Health Service applications were demonstrated to facilitate conversation and explore participants' understanding of mental health and mobile-based mental health interventions. Thematic analysis was used to analyse the interview transcripts. Results: The social ecological model was adopted as an organising framework for the thematic analysis which identified six distinct barriers to older adults' uptake of mobile-based mental health interventions: mental electronic-health (e-health) awareness, interaction with technology, discontinuation, 'seeing' facilitates therapeutic alliance, incongruent role of the general practitioner and privacy and confidentiality. Conclusions: Older adults experience a number of barriers to uptake ranging from the individual level to a macro, organisational level. The practical implications of these barriers are discussed such as the need for increased awareness of mobile-based mental health interventions among older adults.